Allelic variation in sdrD among Staphylococcus aureus from healthy carriers and its role in adhesions - Dori, Almaz Borji (UiT Norges arktiske universitet, 2014)
Summary S. aureus is aerobic, catalase-positive, and oxidase negative organism, and present in the normal microbial flora of the upper respiratory tract and the skin without causing any disease, but at the same time as a potential humans pathogen. S. aureus adheres to the host tissues by means of microbial surface components recognizing adhesive matrix molecules (MSCRAMMs). SdrD is one of three-sdr family proteins, which plays a role in adherence to human nasal epithelial cells. It is assumed that the A-domain of SdrD interacts with a host protein, which is not yet identified. The aim of this study was to investigate whether there is allelic variation in sdrD gene among S. aureus isolates from healthy carriers in Tromsø 6 study and to determine if the sdrD variants differ in their adherence ability to selected human interaction partners. DNA from 51 S. aureus isolates was extracted, and the A-region of sdrD was amplified, purified and the products were sequenced. The sdrD sequences were aligned, and the identities of the sequences were checked using BLAST. To evaluate the contribution of sdrD variants in adhesion, a standard cloning method was used. A full-length sdrD variant was cloned into a shuttle vector and transformed into E. coli then into the gram-positive surrogate host L. lactis. The finding from this study indicates that there is allelic variation in sdrD A-region among S. aureus. From a total of 51 clinical isolates; six different sdrD variants were revealed. Fulllength SdrD1 variants was cloned into a shuttle vector and transformed into E. coli. The transformation of cloned SdrD1 into L. lactis failed and adhesion study could not accomplished.